SUING PATRIARCHY: THE CATCALLING PHENOMENON AND ITS IMPACT ON WOMEN IN MADURA - Awwalin, Imroatil Aziyzil; Yeni Cahya Sukamto; Dina Furqoni Fauzi (Musawa: Journal for Gender Studies, 2025)
The phenomenon of catcalling is a practice of gender-based sexual violence expressed through verbal speech and often occurs in public spaces. This action has serious implications for women's sense of security and dignity, especially in the context of social and cultural relations in Madurese society. In Madura's patriarchal social structure, verbal violence is considered part of ordinary social interactions so that its existence is legitimized by cultural constructions that position women in an unequal position. In essence, this action not only degrades women's dignity but also has a significant impact on psychological, social and cultural aspects. This study aims to answer two main formulations: what is the impact of catcalling in the social, cultural and psychological context on women in Madura? and how does patriarchal culture influence societal behavior towards women in the practice of catcalling?. This research employs a qualitative method with a literature review approach. The analysis was conducted on a number of relevant written sources, including journal articles, research reports, and other academic works. The theoretical framework used to analyze this research is the concept of hegemonic masculinity (Raewyn Connell), patriarchy (Sylvia Walby), and symbolic violence (Pierre Bourdieu). The results of the study indicate that catcalling in Madura is a form of symbolic violence reproduced through a patriarchal value system and socially accepted as normal. It has a significant impact on psychological, social, and cultural conditions. The patriarchal cultural system that views women as objects of sexuality reinforces this behavior and normalizes verbal violence against women. Therefore, educational and cultural interventions are needed that target the structural roots of gender inequality and the formation of more responsive public policies to ensure the protection of women in public spaces.